The Role of Digital Technologies in Enhancing Agricultural Economic Efficiency - William; Kumar, Sharad (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
The integration of digital technologies into agriculture has emerged as a transformative force in enhancing economic efficiency, productivity, and sustainability. Tools such as precision agriculture, Internet of Things (IoT) sensors, artificial intelligence (AI), mobile-based advisory platforms, and blockchain-based traceability systems are redefining how farmers manage resources, monitor crops, and access markets. This paper examines the role of these digital innovations in improving agricultural economic efficiency by reducing input costs, optimizing resource utilization, minimizing post-harvest losses, and increasing farm profitability. Through a review of global and Indian case studies, it highlights how data-driven decision-making and real-time information have significantly boosted yield per input unit and enhanced value-chain transparency. However, challenges persist in digital literacy, infrastructure gaps, affordability, and equitable access for smallholders. The study concludes that inclusive digital adoption—supported by robust data governance, financial incentives, and public–private partnerships—can substantially increase efficiency and resilience in agricultural systems, fostering sustainable economic growth in the agri-sector.